Brand recognition and quality inferences - Yvetta Simonyan; Daniel Goldstein (University of Birmingham, Birmingham Business School, 2013)
Could brands associated with mostly negative information-those with poor reputations-be perceived as superior to unrecognized brands? A reasonable consumer should value reputation; however, it is also sensible to put a heavyweight on brand recognition. To investigate this question, the authors study consumers' inferences about brand quality for products in three domains. Results suggest that brands associated with predominantly negative information are indeed perceived as of higher quality than unrecognised brands. In addition, when consumer inferences are predicted based on different memory cues, the frequency of encountering a brand dominates what people profess to know about it. The authors explore the ecological rationality of this strategy by studying the environmental relationship between expert-judged quality and consumer knowledge.
Keywords: 650; inferences from memory; perceived brand quality; recognition; knowledge valence